Pengaruh Nilai Tukar, Jumlah Uang Beredar, Laju Inflasi, Suku Bunga BI Terhadap Penyaluran Kredit Bank Umum di Indonesia dan IHSG - Immi Fiska Tarigan (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to analyze the exchange rate, money supply, inflation rate, bank interest rates on lending from commercial banks, to the composite stock price index and analyze how much the relationship between lending and the composite stock price index. This research is based on data from 2019 to 2023. This research is categorized as quantitative research with secondary source data obtained from national financial reports. Then the analysis was carried out using multiple linear regression and hypothesis analysis to answer the formulation of research problems. The results show that all factors studied have an influence on bank credit growth. The effect only shows simultaneous influence while partially it does not significantly affect credit growth. as well as all the factors studied have an influence on the composite stock price index both partially and simultaneously. In addition, in the research conducted, credit growth affects the composite stock price index which is quite high, namely 0.629 and this is included in the strong category.